Augmenting Osteochondral Autograft Transplantation and Bone Marrow Aspirate Concentrate with Particulate Cartilage Extracellular Matrix Is Associated With Improved Outcomes. (September 2022) - Drakos, Mark C.; Hansen, Oliver B.; Eble, Stephanie K.; Kukadia, Saanchi; Cabe, Taylor N.; Kumar, Prashanth; Patel, Karan A.; Sofka, Carolyn M.; Deland, Jonathan T.
Background: Osteochondral autograft transplant (OAT) is often used to treat large osteochondral lesions of the talus and is generally associated with good outcomes. The addition of adjuncts such as cartilage extracellular matrix with bone marrow aspirate concentrate (ECM-BMAC) may further improve the OAT procedure but have not been thoroughly studied. We hypothesized that the placement of ECM-BMAC around the OAT graft would improve radiographic and patient-reported outcomes following OAT. Methods: Patients who received OAT, with ECM-BMAC or BMAC alone, were screened and their charts were reviewed. For patients who did receive ECM-BMAC, the mixture was spread around the edges of the OAT plug and into any surrounding areas of cartilage damage. Survey and radiographic data were collected. Average follow-up in both groups was over 2 years. Magnetic resonance imaging scans were scored using the Magnetic Resonance Observation of Cartilage Tissue (MOCART) system. Outcomes were compared statistically between groups. Results: Patients treated with ECM-BMAC (n = 34) demonstrated significantly greater improvement of scores in the FAOS categories Symptoms (17 vs −3; P = .02) and Sports Activities (40 vs 7; P = .02), and the MOCART category Subchondral Lamina ( P = .008) compared to those treated with BMAC alone (n = 30). They also experienced significantly lower rates of postoperative cysts (53% vs 18%, P = .04) and edema (94% vs 59%, P = .02). Conclusion: The addition of ECM-BMAC to OAT was associated with improved imaging and clinical outcomes compared to OAT with BMAC alone.